Hubungan Stres dengan Temporomandibular Disorder Pada Narapidana di Lembaga Pemasyarakatan Perempuan Kelas II B Padang - Aisyah Triana; Eni Rahmi; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2020)
Stress is known as a risk factor for temporomandibular disorder. Prisoners who live in Correctional Institutions have a high risk of experiencing stress because of the existing pressure. The purpose of this study was to determine the relationship between stress and temporomandibular disorder in prisoners at Class IIB Correctional Institutions in Padang. This study was a cross-sectional study. The instrument that use to measured stress on inmates was the Perceived Stress Scale 10 (PSS-10), while to determine the diagnosis of TMD using RDC/TMD Axis I. The result showed that 7 respondents (23,3%) had mild stress, 20 respondents (66,7%) had moderate stress, and 3 respondents (10%) had severe stress. Respondents who experienced TMD were 19 respondents (63,3%). The most common type of TMD diagnosis is the disc displacement with reduction. Kolmogorov-Smirnov statistical test results obtained p=0,164 (p>0,05) which means there is no significant relationship between stress and temporomandibular disorder in prisoners at Class IIB Women’s Penitentiary in Padang. This study concludes that stress is not related to the temporomandibular disorder in prisoners at Class IIB Women’s Penitentiary in Padang.